Modeling the atmospheric response to solar irradiance changes using a GCM with a realistic QBO - Palmer, M; Gray, L (2005)
The impact of solar irradiance changes on the winter polar stratosphere is investigated using a general circulation model in which the equatorial Quasi-Biennial Oscillation (QBO) is internally generated and self-sustaining. The model results compare favorably with observations, supporting previous findings that the equatorial zonal wind modulates the polar stratospheric response to solar irradiance changes. In the QBO easterly phase, Northern Hemisphere sudden stratospheric warmings are found to be more prevalent under solar minimum conditions than under solar maximum conditions. However, in the QBO westerly phase the reverse is true. The possible solar-modulation of the QBO period is also investigated. Although small changes are evident in the same sense as those observed, i.e. a lengthening of the period during solar minimum conditions, longer simulations would be required to verify the statistical significance of this result. Copyright 2005 by the American Geophysical Union.